Knowledge, attitude, and practice toward food poisoning among food handlers and dietetic students in a public university in Malaysia - Mohd Yusof, Aimi Maisarah; A. Rahman, Nor Azlina; Haque, Mainul (Wolters Kluwer - Medknow, 2018)
Background: Food poisoning (FP) commonly occurs because of consuming contaminated food, which can be fatal. Many people are not aware of the dangers of FP. Thus, the purpose of this study is to analyze the knowledge, attitude, and practice (KAP) of FP among dietetic students (DS) and food handlers (FH) in a public university in Malaysia. Materials and Methods: A cross-sectional study was designed, and a self-administered questionnaire was distributed to 106 respondents. The survey comprised four sections including sociodemographic, knowledge, attitude, and practice. Results: Total percentage scores for KAP for FH were 86.06%, 32.40%, and 19.91%, respectively, whereas the KAP scores for DS were 89.36%, 34.26%, and 19.94%, respectively. This study revealed that the respondents had good knowledge but poor attitude and practice toward FP. Total mean percentage of KAP scores for DS was higher than FH. Besides, no significant difference was observed in KAP toward FP across different genders, age, education, and income levels among FH. However, for DS, significant difference (p = 0.008) was observed in knowledge toward FP between genders. Significant association (p = 0.048) was also reported in practice toward FP with age among DS. This study also found a significant association between knowledge and attitude (p = 0.032) and knowledge and practice (p = 0.017) toward FP among FH. Conclusion: Nevertheless, among DS, no significant association was observed between knowledge, attitude and practice toward FP. The findings may help them to plan effective methods to promote better understanding about FP and improving their knowledge and awareness.